Behavioral Influences on Individual Investors' Decision-Making - Guna Raj Chhetri, (Journal of Development and Administrative Studies, 2024)
The performance and decision-making of individual investors in Nepal are investigated in this study, with an emphasis on the behavioural aspects that affect their investing decisions. Determiners of investment performance and decisions, the interaction between market, firm, and risk-return variables, and their influence on investor choices are the objectives of the study. 110 respondents, including commercial banks, business owners, government employees, graduate management students, and stock market investors, were selected from the Bharatpur metropolitan area in the Chitwan district using a descriptive and causal comparative study approach. The results indicate that market trends have a considerable impact on investing confidence, as seen by the moderately positive correlation found between investor decisions and market-related variables (MRV). The significance of a company's performance metrics, management quality, and reputation is highlighted by the greater positive correlation found for company-related variables (CRV). Additionally, there is a moderately positive correlation between risk and return variables (RRV), indicating that people who are more confident in their investing decisions are more likely to be willing to face risks in exchange for larger returns or who prefer steady returns. According to the study's findings, investor decisions are significantly influenced by a variety of interrelated factors, including firm characteristics, market conditions, and risk-return preferences.